Polymorpishm of D-Loop Mitochondrial DNA Region and Phylogenetic in Five Indonesian Native Duck Population - Hartatik, Tety (2013)
This research aimed to determine mitochondrial DNA (mtDNA) D-loop region polymorphism and phylogeneticin five Indonesian native ducks population namely Magelang duck, Tegal duck, Mojosari duck, Baliduck and Alabio duck. The significance of this research was applicable to conservation and refinement strategyas well as the improvement of genetic quality by utilizing the available native duck plasma nutfah. Itfurther concerned with determining the genealogy of family, channel, breed or maternal inheritance that bredindividuals in native duck population in Indonesia and discovering phylogenetic relations with Mallards duck(Anas platyrhynchos) and the other Anasducks. Fragment of 718-bp was amplified by PCR and determined the nucleotide sequence of 701-bp. The sequence was then analyzed using Single Nucleotide Polymorphism (SNP) and compared to the standard nucleotide sequence from Anas Platyrhynchoscomplete genome(HM010684.1) in GenBank Accession. It obtained nucleotide percentage equation of 93.59±8.23%. Phylogenetic investigation used sequencing products and was analyzed using MEGA5 software. Indonesian nativeducks have a relatively close genetic relationship with Anas Platyrhynchosand Anas zonorhyncha shownbythe genetic distance varying from 0.000-0.786 compared to the other Anasducks in the world (0.073-1.037)or to Cairina moschata(2.972-5.776). Highly distant genetic variation was found in Magelang duckcomparedto the other native ducks ranged from 0.000-0.950 to 0.000-0.312. The research concluded thatpolymorphism of mtDNA D-loop region was found in Indonesian native ducks and had relatively similar maternal inheritance with Anas platyrhyncos danAnas zonorhyncha. Key words:Polymorphism, D-loop DNA mitochondria, phylogenetic, native ducks in Indonesia